Tecnologías de la información y comunicación y gestión de procesos en el RENIEC Pucallpa 2022 - Rengifo Lino, Rodolfo (2023)
The research project aimed to determine the relationship between information and communication technologies and process management in the RENIEC Pucallpa 2022, the type of study I took was applied, the level was descriptive correlational, with a non-experimental design, its population was made up of 15 workers of that institution, for the collection of data the survey and the questionnaire were used as an instrument. Concluding that, ICT in the RENIEC has been qualified as a means, since the entity sometimes designates the authorized personnel to make the delivery of the resources, however, it almost never facilitates citizen participation in public affairs, but they always use the means of social communication, and sometimes encourages cooperation between co-workers. On the other hand, process management is considered regular (27%) since it sometimes has a strategic plan according to the context; in addition, strategies are almost never established to achieve goals and objectives; sometimes it promotes professional development through constant training. Finally, it was determined that the relationship between information and communication technologies and process management in the RENIEC of the city of Pucallpa in 2022 is clear, being contrasted by the Pearson correlation considerable positive level (r = 0.863; p = 0.000).